Impalement injuries of the oral cavity in children: a case report and survey of the literature - O. JAMES YOUNESSI, & EDUARDO A.ALCAINO (IAPD and Blackwell, 2007)
Impalement injuries of the soft palate and oropharynx are common in children, especially those of preschool age. These injuries are particularly common in toddlers, given their propensity to fall easily while carrying objects in their mouths. Although most of these injuries do not have lasting sequelae, some can have devastating neurological complications, and consequently, careful assessment of the patient during the early stages of trauma is imperative.